SUCCESSFUL AGING: CROSS-CULTURAL COMPARISON OF OLDER ADULTS' LAY PERSPECTIVES. (11th November 2018) - Jensen, A; Claunch, K; Verdeja, M; Dungan, M; Goates, M; Thacker, E
Abstract: Biomedical views of successful aging include physiological, psychological and social constructs, but do not capture older adults' lay perspectives, and omit culture-specific concepts. Therefore, our objective was to determine how older adults express the concept of successful aging and to compare their views across cultures. We conducted a literature review of original articles published from 2010 onward in which researchers asked older adults open-ended questions such as "what does successful aging mean to you?" In 32 articles we reviewed, we identified several lay perspectives that were similar across countries and cultures: social engagement (highlighted in 22 articles), attitude (17), physical function (12), cognitive function (10), spirituality (10), independence (9), and financial security (8). Additionally, social engagement was most frequently mentioned within all major world regions we studied, including North America, Latin America, Western Europe, North Africa/Middle East, and Asia/Oceania. In contrast, certain lay perspectives were more common to specific world regions. For example, older adults from North America and Latin America mentioned spirituality more often, whereas older adults from Western Europe, North Africa/Middle East, and Asia/Oceania were more likely to mention physical function. Finally, some perspectives were unique to specific countries. For examples, to Japanese older adults, "arriving at a conclusion in life" added meaning to their aging experience, while older adults in Puerto Rico valued gratitude towards life. In conclusion, older adults' lay perspectives on successful aging are richer and more complex than a biomedical view would suggest, and are influenced by cultural context.